2020
DOI: 10.1007/s10494-020-00192-4
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Heat Loss Effects in the Large Eddy Simulation of a Lean Swirl-Stabilised Flame

Abstract: The flame in a gas turbine model combustor close to blow-off is studied using large eddy simulation with the objective of investigating the sensitivity of including different heat loss effects within the modelling. A presumed joint probability density function approach based on the mixture fraction and progress variable with unstrained flamelets is used. The normalised enthalpy is included in the probability density function to account for heat loss within the flame. Two simulations are presented that use fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…These simulations demonstrated that the flame stabilisation and lift-off processes are highly influenced by the PVC. Furthermore, it has been demonstrated that including heat loss effects can influence the flame shape [25] and stability [24,26,27]. It is expected that the PVC attributes will be affected by heat loss as previously hinted [24].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…These simulations demonstrated that the flame stabilisation and lift-off processes are highly influenced by the PVC. Furthermore, it has been demonstrated that including heat loss effects can influence the flame shape [25] and stability [24,26,27]. It is expected that the PVC attributes will be affected by heat loss as previously hinted [24].…”
Section: Introductionmentioning
confidence: 75%
“…Hence, the fluid mechanical processes in the GTMC are complex and challenging for numerical modelling. However, recent studies [21][22][23][24] have demonstrated that these flow features and flame characteristics can be captured well using a carefully designed flamelet based SGS combustion closure. These simulations demonstrated that the flame stabilisation and lift-off processes are highly influenced by the PVC.…”
Section: Introductionmentioning
confidence: 99%
“…Heat loss effects are implemented in a similar fashion to that used in Ref. 19 by scaling down the heat release rate in the energy equation. As can be seen in the figure, the computed adiabatic flame speeds agree well with the measurements and as the heat loss increases, the flame speed drops smoothly.…”
Section: Les Framework and Numerical Setupmentioning
confidence: 99%
“…They showed that the heat loss effects are important for the swirl burners considered and need to be taken into account in the LES in order to correctly capture the thermoacoustic instability. Thus, a non-adiabatic flamelet approach is adopted from Massey et al 19 for this work and the heat loss effects on the instability simulation are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The heat loss effects on the stabilization of a lean swirl-stabilized flame close to blow-off conditions was analyzed by Massey et. al [24], showing that the lift-off height is influenced by the wall heat transfer modelling. DNS was used to perform a sensitivity analysis of transfer functions of laminar flames [12], proving that the inlet air temperature affects both gas velocity and flame speed whereas the combustor wall-temperature determines the lift-off distance of the flame and controls the FTF delay.…”
mentioning
confidence: 99%